2010
DOI: 10.1016/j.rbmo.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved development of mouse and human embryos using a tilting embryo culture system

Abstract: Mammalian embryos experience not only hormonal but also mechanical stimuli, such as shear stress, compression, and friction force, in the fallopian tube before nidation. In order to apply mechanical stimuli to embryos in a conventional IVF culture system, we developed the Tilting Embryo Culture System (TECS). The observed embryo images from the TECS suggest that the velocities and shear stresses of TECS embryos are similar to those experienced in the oviduct. Use of TECS enhanced the development rate to the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 19 publications
3
69
0
Order By: Relevance
“…During mouse embryonic development, the number of mouse embryos in a 50 μL MTF droplet was limited to 5 to minimize the influence of group culture [36,37] and to maximize the effect of the experimental conditions between the static culture and the micro-vibration culture [20]. The mouse embryonic development rate when the O 2 pressure is low (5 %) is commonly faster than when the O 2 pressure is high (20 %) [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During mouse embryonic development, the number of mouse embryos in a 50 μL MTF droplet was limited to 5 to minimize the influence of group culture [36,37] and to maximize the effect of the experimental conditions between the static culture and the micro-vibration culture [20]. The mouse embryonic development rate when the O 2 pressure is low (5 %) is commonly faster than when the O 2 pressure is high (20 %) [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a micro-vibration embryonic culture method that mimics in vivo mechanical forces would be a valuable approach to improving the quality of in vitro fertilization (IVF) treatment. Other dynamic culture systems have been recently reported, including a microfluidic dynamic embryonic culture system [44,45] and a tilting embryonic culture system [20]. Each system has pros and cons and presents challenges for practical use [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive effects using tilting culture systems were also found in a microdroplet environment. We developed a tilting embryo culture system (TECS) to move mouse, porcine, and human embryos by fluid motion of the microdroplet, and we have shown that blastocyst development rates of these embryos using TECS improved over those of static controls [85][86][87]. Gentle vibration of porcine and human embryos also appeared to yield improved blastocyst formation rates [88][89][90].…”
Section: Elastomer Channels and Devices For Dynamic Embryo Culture Symentioning
confidence: 99%
“…Several groups have tried to apply a variety of methods, such as mechanical microvibrations to embryo culture plates [6][7][8], the use of dynamic fluids in embryo culture [9][10][11][12][13][14][15][16] or the use of a tilting embryo culture system [17]. An improvement in the quality of in vitro human blastocysts was noted when the tilting embryo culture system was used [18,19] and also when dynamic microfunnel culture conditions were applied [12]; in the latter study a higher rate of embryo implantation and subsequent pregnancy was also noted. Pregnancy rates were as well increased with the application of pulsatile mechanical microvibrations to the culture system (20 Hz over 5 seconds, once per hour) [6].…”
Section: Introductionmentioning
confidence: 99%